EFEKTIFITAS PENGGUNAAN AUSTRALIAN TRIAGE SCALE (ATS) MODIFIKASI TERHADAP RESPON TIME PERAWAT DIINSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT HATIVE PASSO TAHUN 2021 - Abdul Thalib; Yona Latuperisa; Oldrin Latue (STIKES Pasapua Ambon, 2022)
Introduction: The emergency department is an important unit in the operation of a hospital, namely as the entry point for every service that operates 24 hours apart from general polyclinics and specialists which only serve patients during working hours. The emergency room must serve all cases admitted to the hospital. Method: observational analytic This research will be conducted at Hative Passo Hospital in November 2021. Results: The results of the hypothesis test using the chi-square test show a p value = 0.003 <α = 0.05. Thus it can be concluded that there is a significant relationship between the use of the Australian Triage Scale (ATS) and the response time of nurses in the emergency room of Hative Passo Hospital. Conclusion: Australian Triage Scale (ATS) has a significant relationship with nurse response time